Bank Soundness Level Analysis Using Method Risk-Based Bank Rating (RBBR) at PT Bank Negara Indonesia (Persero), Tbk period 2018-2020 - Eva Khadijah; Dhea Afifah (Asosiasi Dosen Muda Indonesia, 2022)
Banks are one of the institution holding finance _ role important in Indonesian economy . As one related industries with finance, banks are wheel mover economy national, so could said as his heart service finance. Study this aim for knowing evaluation level bank health at PT Bank Negara Indonesia (Persero), Tbk seen from factor Risk Profile, Good Corporate Governance, Earnings, and Capital period 2018-2020. Type used is study quantitative with using secondary data sourced from report finance Annual Report PT Bank Negara Indonesia (Persero), Tbk period 2018-2020. The method used in the research this is the RBBR (Risk-Based Bank Rating) method and uses NPL, LDR, GCG, ROA, NIM, and CAR variables that produce evaluation for knowing level bank health. Research results level bank health at PT Bank Negara Indonesia (Persero), Tbk the period 2018-2020 obtained results rating composite 1 (PK-1) reflecting that by general bank condition in